2022
DOI: 10.3389/fphys.2022.980755
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor performance at high altitude in COPD patients. Randomized placebo-controlled trial of acetazolamide

Abstract: Introduction: We evaluated whether exposure to high altitude impairs visuomotor learning in lowlanders with chronic obstructive pulmonary disease (COPD) and whether this can be prevented by acetazolamide treatment.Methods: 45 patients with COPD, living <800 m, FEV1 ≥40 to <80%predicted, were randomized to acetazolamide (375 mg/d) or placebo, administered 24h before and during a 2-day stay in a clinic at 3100 m. Visuomotor performance was evaluated with a validated, computer-assisted test (Motor-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…A major strength of our trial is to provide robust evidence of altitude-related deterioration of postural control in a large group of older individuals and to show that AZA mitigates this adverse effect of hypobaric hypoxia. This study was part of a larger trial investigating the efficacy of preventive AZA treatment in reducing AMS (Furian et al, 2022) and participants underwent various assessments other than just the balance board measurements including exercise tests which may have affected performance in postural control due to muscular fatigue (Paillard, 2012). Since postural control was assessed before exercise tests and because the same tests were performed at both altitudes and in both groups, it is unlikely that the various assessments have affected the conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A major strength of our trial is to provide robust evidence of altitude-related deterioration of postural control in a large group of older individuals and to show that AZA mitigates this adverse effect of hypobaric hypoxia. This study was part of a larger trial investigating the efficacy of preventive AZA treatment in reducing AMS (Furian et al, 2022) and participants underwent various assessments other than just the balance board measurements including exercise tests which may have affected performance in postural control due to muscular fatigue (Paillard, 2012). Since postural control was assessed before exercise tests and because the same tests were performed at both altitudes and in both groups, it is unlikely that the various assessments have affected the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…This study was part of a randomized, placebo-controlled, double-blinded trial evaluating the efficacy of preventive AZA treatment in reducing AMS in healthy lowlanders 40 years of age or older during a 2-day sojourn at 3,100 m (Too Ashu High Altitude Clinic, Kyrgyz Republic). Data on effects of altitude and AZA on AMS and physiologic outcomes have been reported elsewhere (Furian et al, 2022). Data on postural control, the focus of the current study, have not been published.…”
Section: Study Design and Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The rise in ventilation induced by acetazolamide improves systemic and cerebral oxygenation [14,15] and may therefore partially reverse the altitude-induced hypobaric hypoxia of the neuromuscular system and its clinical manifestations. Consistently, in patients with chronic obstructive pulmonary disease (COPD) travelling to 3,100 m, we found that preventive treatment with acetazolamide improved oxygenation, visuomotor performance, learning and postural control compared to placebo [16,17]. In healthy individuals, the few studies on effects of acetazolamide on cognition at high altitude are inconclusive because of the small number of participants and methodological limitations [18,19].…”
Section: Introductionmentioning
confidence: 93%